Analisis Satuan Acara Perkuliahan Mata Kuliah Korespondensi Bisnis Jepang di 7 Perguruan Tinggi Se-Jabodetabek - Elisa Carolina Marion (Bina Nusantara University, 2010)
Japanese Business Correspondence is a course that is given by 7 Japanese language study institutions all around Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi). Each institution has their own uniqueness which can be seen in course unit composition. The research method used in this research is survey. The result of this research is that most institutions teach the general correspondence rather than business correspondence. It is also found that there are 2 institutions having uniqueness compared with the other five institutions. The two institutions are STBA LIA and BINUS University. The speciality of STBA LIA is the subject related to verbal correspondence. Meanwhile, BINUS University is more specialized in email-format correspondence.